Consensus statement Immunonutrition and exercise - Bermon, S.; Castell, L. M.; Calder, P. C.; Bishop, N. C.; Blomstrand, E.; Mooren, F. C.; Krüger, K.; Kavazis, A. N.; Quindry, J. C.; Senchina, D. S.; Nieman, D. C.; Gleeson, M.; et al. (Exercise Immunology Review, 2017)
In this consensus statement on immunonutrition and exercise, a panel of knowledgeable contributors from across the globe provides a consensus of updated science, including the background, the aspects for which a consensus actually exists, the controversies and, when possible, suggested directions for future research.